Imported schistosomiasis in Paris region of France: A multicenter study of prevalence and diagnostic methods. Issue 41 (May 2021) - Leblanc, Claire; Brun, Sophie; Bouchaud, Olivier; Izri, Arezki; Ok, Vichita; Caseris, Marion; Sorge, Fréderic; Pham, Luu-ly; Paugam, André; Paris, Luc; Jaureguiberry, Stéphane; Bloch-Queyrat, Coralie; et al.
Abstract: Background: There are few data on imported schistosomiasis – especially in children. The objectives of the present study were to estimate the prevalence of imported schistosomiasis in at-risk children in the greater Paris region of France and to compare diagnostic methods. Method: Children at risk of schistosomiasis who consulted or were hospitalized in four hospitals in the greater Paris region were prospectively included. Clinical and laboratory data were collected. Urine and feces samples were screened for Schistosoma spp. using microscopy, a point-of-care circulating cathodic antigen and a real-time polymerase chain reaction assay. Serum samples were screened using Western blot, ELISA, indirect hemagglutination, and immunochromatographic assays. The diagnosis was characterized as confirmed (positive microscopy analysis) and as suspected (positive ELISA and Western blot assays). The prevalence of schistosomiasis and the tests' performances were estimated using the latent class method. Results: A total of 114 children were included. Most of the children were newly arrived migrants from sub-Saharan Africa. The mean age was 13.2 years-old. There were 12 (10.5%) confirmed cases and 13 (11.4%) suspected cases. Half of the confirmed and suspected cases were asymptomatic. The prevalence was 24.3%. The ELISA and the Western blot assays presented the same sensitivity (83%) and specificity (99%). The serum immunochromatographic assay also showed good performance. Conclusions: The high prevalence of imported schistosomiasis among at-risk children in the greater Paris region confirms the need for systematic screening. A serum immunochromatographic assay appears to be one of the most effective screening methods for a low cost.